Desarrollo de un programa de educación ambiental sobre la importancia de la zarigueya (Didelphis marsupialis) como controlador biológico en la comunidad Puerto Loor - Delgado Solórzano, Guillermo Abelardo (2021)
The purpose of the work was the development of an environmental education program on the importance of the opossum (Didelphis Marsupialis) as a biological controller in the Puerto Loor community. This research was non-experimental, using analytical-synthetic, deductive and exploratory methods, applying survey techniques and documentary review. For the application of this work, an initial diagnosis was made to a sample of 267 inhabitants to identify the knowledge about the ecological value of the opossum, obtaining as a result a 92.93% ignorance. Subsequently, an environmental education program was developed to understand the ecological value of the opossum, with the participation of 652 inhabitants, a matrix was made that helped to systematize, synthesize and organize the information, using didactic tools that facilitated perception and understanding of the facts. Finally, the knowledge acquired by the residents of the community was evaluated, applying a posttest that resulted in an excellent performance level of 93.71%. Environmental education programs make it possible to raise awareness about the importance, benefits and roles that species have in the environment and thus help the conservation and preservation of ecosystems.